A Case Report of Fibrous Dysplasia in an Acetabulum with Mild Hypoplasia of the Hip Treated with Bone Graft and Rotation Acetabular Osteotomy - MAJIMA Tokifumi; 清藤 直樹; 大浦 久典; 井上 正弘; 三浪 明男 (Japanese Journal of Rheumatism and Joint Surgery, 2007)
A case of fibrous displasia (FD) in the acetabulum with mild hip dysplasia treated with curettage, bone graft and rotation acetabular osteotomy of the pelvis is reported. A 21-year-old female complained of left hip pain. Plain x-rays showed well-defined rarefaction in the acetabulum. The size was 21mm in length and 17mm in width. The plain x-rays also showed mild acetabular hypoplasia with 19 degrees of center-edge angle and 48 degrees of acetabular angle. 3D CT showed obvious hypoplasia in the anterior acetabulum. Eight years after surgery, there has been no re-currence of FD and no progression of osteoarthritis of the hip.